Effect of Holding Time in Pack Carburizing Using Bamboo Charcoal on the Mechanical Properties of ST 41 Steel - Feris Kurniaawan; Muhamad Fajar Sidiq; Irfan Santosa (Asian Journal of Mechanical Engineering, 2025)
This study investigates the effect of holding time in the pack carburizing process using bamboo charcoal on the mechanical properties of ST 41 steel. The carburizing treatment was conducted at a temperature of 850 °C using a solid carburizing medium consisting of bamboo charcoal and barium carbonate in an 80:20 ratio. Holding time variations of 45, 65, and 85 minutes were applied. After carburizing, the specimens were quenched in SAE 20W-50 oil and subsequently tempered at 350 °C for 20 minutes. Mechanical characterization included Vickers hardness testing, wear testing, and impact testing. The results indicate that holding time has a significant influence on the mechanical properties of ST 41 steel. The average hardness increased with longer holding time, from 162.0 VHN for untreated material to 175.2 VHN at 45 minutes, 185.5 VHN at 65 minutes, and 196.5 VHN at 85 minutes. Wear test results showed a reduction in wear rate with increasing holding time, reaching the lowest value of 0.000029 mm³/kg·m at 85 minutes. In contrast, impact strength decreased as holding time increased, from 3.302 J/mm² for untreated steel to 2.934 J/mm² at 85 minutes. These results demonstrate that longer holding time in pack carburizing enhances surface hardness and wear resistance of ST 41 steel but reduces its impact toughness. An 85-minute holding time provides the best hardness and wear resistance, although accompanied by a decrease in impact strength. This study provides a reference for optimizing heat treatment parameters to improve the performance of mechanical components, particularly gears.